Analisis Produk Tabungan Dan Produk Pembiayaan Pada PT. Bank Muamalat Kolaka, Sulawesi Tenggara - Ibrahim Tawile; Samsidar sidar; Muh Yusuf (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
KPR Muamalat iB is a financing product that will help you to have houses, flats, apartments and condotels including renovation and construction and take-over of mortgages from other banks with two choices of contracts, namely murabahah (buying and selling) or musyarakah contract mutanaqishah (rental cooperation). And KPR muamalat IB also provides various offers which are based on sharia and installments that are up to 15 years in length. And installments remain until the end of financing in accordance with the agreement with murabahah contract. And of course with a down payment of up to 10%. KPR.